Evaluation of urban heat island situation in developed cities of Zhejiang province - Shen, Tianfeng (2015)
The rapid and unsustainable urbanization process causes a serious existing thermal environmental problem that aggravates climatic change and generates a higher temperature in urban area than in rural area. Based on literature review, this is the first research that uses field measurement methodology to investigate the urban heat island (UHI) effect in Hangzhou and Ningbo cities of Zhejiang Province. This study aims to investigate reciprocal interaction of UHI effect with urban building energy based on the air temperature and relative humidity measurement in research area.